Service Quality Analysis of Business Licensing Information System (BLIS) at the Provincial Industry Department Using Decision Tree - Putri, Indah Pratiwi; Marcelina, Dona; Yulianti, Evi; Anandez, Arum Adisha Putra (Acceleration, Quantum, Information Technology and Algorithm Journal, 2024)
In the digital era, government services, particularly business licensing, are expected to be efficient, reliable, and user- friendly to meet public demands. The South Sumatra Provincial Industry Department has adopted a web-based Business Licensing Information System to facilitate the licensing process. However, the system’s effectiveness in delivering quality service and ensuring process efficiency remains underexplored. This study aims to evaluate the service quality of the system, focusing on factors such as reliability, responsiveness, assurance, empathy, and usability. Using decision tree analysis, the study identifies the key variables impacting user satisfaction and process efficiency. The research objectives include assessing the overall quality of the service, analysing factors influencing efficiency, and providing recommendations for system improvement. Data will be gathered from business users who have utilized the system within the past year. The study scope encompasses service quality dimensions, process efficiency indicators, and user satisfaction metrics. Decision tree analysis will be employed to analyse these variables, highlighting the most influential factors on system performance. This research is expected to provide insights for enhancing the system’s reliability and usability, offering data-driven recommendations for decision-makers at the Industry Department. By improving the system, users can experience a more streamlined and satisfying licensing process, ultimately increasing their likelihood to recommend and reuse the service. The findings will also contribute to public information systems literature, serving as a valuable reference for similar service evaluations and optimizations in other government sectors